2018
DOI: 10.1186/s13104-018-3910-8
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial profile, antibiotic susceptibility pattern and associated factors among pregnant women with Urinary Tract Infection in Goba and Sinana Woredas, Bale Zone, Southeast Ethiopia

Abstract: ObjectiveUrinary tract infection (UTI) is one of the commonest infections affecting millions worldwide, especially pregnant women. It can lead to poor maternal and perinatal outcomes. Untreated UTI can be associated with serious obstetric complications. So the objective of present study was to determine the bacterial profile, antibiotic susceptibility pattern and associated factors of UTI among pregnant women in Goba and Sinana Woredas, Bale Zone, Southeast Ethiopia.ResultsThe overall prevalence of UTI was 44/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
38
10
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(69 citation statements)
references
References 16 publications
13
38
10
8
Order By: Relevance
“…This finding is comparable with a study conducted in Dessie, Ethiopia, 5 Hawassa, Ethiopia, 6 and Bale, Ethiopia. 36 However, most Gram-negative bacteria were resistant to amoxicillin (79.3%), amoxicillin-clavulanic acid (37.9%).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is comparable with a study conducted in Dessie, Ethiopia, 5 Hawassa, Ethiopia, 6 and Bale, Ethiopia. 36 However, most Gram-negative bacteria were resistant to amoxicillin (79.3%), amoxicillin-clavulanic acid (37.9%).…”
Section: Discussionmentioning
confidence: 99%
“…In our study out of 730 samples, 238 (33%) showed significant bacteriuria which was higher than Afroza et al (6.87%) 10 , Arshi et al (30%), 11 Angamiet et al (28.1%) 12 but lower than Nzalie et al (58.8%), 13 Maheswary et al (63.51%), 15 Prakash et al (53.82%), 16 Taye et al (36%), 16 khan et al (54.4%), 17 Manjunath et al (42.37%) 18 it was very similar to Dash et al (34.5%) 19 most probably due to similar environmental niche. BYC was positive in 2 % growth and it was lower than Manjunath et al (4.5%) 18 and Venkatesh et al (6%).…”
Section: Discussionmentioning
confidence: 45%
“…The least common bacteria was Citrobacter (1%).This finding was very similar with Dash et al 19 (68.8% E. coli followed by 9.7% Enterococci), Manjunath et al (60.7% E. coli followed by 12.1% Enterococci species) 18 and Arshi et al(56.7% E. coli followed by 13.1% Enterococci species) 11 but not consistent with the most of the studies worldwide. Klebsiella was the 2 nd most common bacteria in Nzalie et al 13 Angamiet et al, 12 Prakash et al, 15 Taye et al, 16 Jubina et al 21 , khan et al, 17 Mahajan et al 28 Akochere ET al 29 showed that Klebsiella was the least prevalent (1.2%) bacteria in UTI. Ehinmidu ET al 30 showed that Pseudomonas was the most common (32%) bacteria in UTI.…”
Section: Discussionmentioning
confidence: 99%
“…Several microorganisms have been associated with UTI although Escherichia coli is the most frequent accounting for 80 % to 90 % of UTI's in pregnancy [1,[9][10][11].…”
Section: акушерство гинекология и репродукцияmentioning
confidence: 99%
“…044 AP/MINSANTE/HGD/DM/03/19). We respected the ethical principles of the Helsinki declaration while carrying out this study [10] and reporting was according to the Strobe guidelines for a case-control study.…”
Section: Ethical Aspects/ этические аспектыmentioning
confidence: 99%